Non-linear parametric resonance driven oscillations of dumbell satellite in elliptical orbit under the combined effects of magnetic field of the earth and oblateness of the earth - Narayan, A.; Pandey, M. D. (International Journal of Advanced Astronomy, 2015)
Parametric resonance driven oscillations of a dumbbell satellite in elliptical orbit in central gravitational field of force under the combined effects of perturbing forces Earth Magnetic field and Oblateness of the Earth has been studied. The system comprises of two satellite connected by a light, flexible and inextensible cable, moves like a dumbbell satellite in elliptical orbit, in central gravitational field of force. The gravitational field of the Earth is the main force governing the motion and magnetic field of the Earth and Oblateness of the Earth are considered to be perturbing forces, disturbing in nature. Non-linear oscillations of dumbbell satellite about the equilibrium position in the neighborhood of parametric resonance \(w=1/2\), under the influence of perturbing forces, which is suitable for exploiting the asymptotic methods of Bogoliubov, Krilov and Metropoloskey has been studied, considering ‘e’ to be a small parameter. The Hamiltonian has been constructed for the problem and phase analysis has been applied to investigate the stability of the system.